2006
DOI: 10.1007/bf03178891
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two-dimensional transmitted dose maps: evaluation of existing algorithms

Abstract: Composite analysis and the gamma function are often used to assess the agreement between a reference and an evaluated two-dimensional dose maps. The intent of the study is to compare advantages, disadvantages and limitations of dose evaluation tools reported in the literature. In addition, in order to improve the gamma function output, a "Signed Matrix" was introduced using the ratio of relative dose difference maps. Transmitted dose maps were acquired for a range of homogeneous phantoms using Extended Dose Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
(20 reference statements)
1
1
0
Order By: Relevance
“…It has been shown that in the presence of homogenous attenuators, there is a reasonable agreement between EPID and TPS dose values for large radiation fields. [43,44] The results prove that the calibration method used in this study guaranties sufficient accuracy when using the EPID dosimetry.…”
Section: Resultssupporting
confidence: 52%
“…It has been shown that in the presence of homogenous attenuators, there is a reasonable agreement between EPID and TPS dose values for large radiation fields. [43,44] The results prove that the calibration method used in this study guaranties sufficient accuracy when using the EPID dosimetry.…”
Section: Resultssupporting
confidence: 52%
“…In addition, although the gamma function is a powerful tool to recognize the agreed and disagreed areas, it is not able to separate the over and underdose regions. [16] Moreover, if there is a search for a consistent dose value in neighboring points in a two-dimensional area, this cannot be extended into a volume. The hypothesis of this study is that “with extension into the third dimension, consideration of the “less or more” fluctuations in the z direction, caused by patient positioning, organ motion, couch positioning, and isocenter calibration, for the point dose displacement in the z dimension can be achieved”.…”
Section: Introductionmentioning
confidence: 99%